A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan - Cheng, Zhi-Fei; Peng, Zhong (Zootaxa, 2019)
Material of the paederine genus Paederus Fabricius, 1775 of mainland China and Taiwan was examined. In total, seven species are recognized, among which one is described here as new: P. (Gnathopaederus) zhangmuensis sp. n. (Xizang: Zhangmu). New provincial records are provided for P. jianyueae Peng and Li, 2014 from Fujian.